LMO1 Gene Polymorphisms Reduce Neuroblastoma Risk in Eastern Chinese Children: A Three-Center Case-Control Study - He, Lili; Zhu, Jinhong; Han, Fei; Tang, Yingzi; Zhou, Chunlei; Dai, Jincheng; Wang, Yizhen; Zhou, Haixia; He, Jing; Wu, Haiyan (Frontiers in Oncology, 2018)
Background: Neuroblastoma, a neuroendocrine tumor, stems from the developing sympathetic nervous system. Previous genome-wide association studies (GWASs) have discovered a number of neuroblastoma susceptibility genes in Caucasians including LIM domain only 1 (LMO1). Objective: We conducted a three-center case-control study including 313 cases and 716 controls with the purpose to evaluate the association between five GWAS-identified LMO1 variants (rs110419 A>G, rs4758051 G>A, rs10840002 A>G, rs204938 A>G, and rs2168101 G>T) and neuroblastoma susceptibility in eastern Chinese children. Methods: Odds ratios (ORs) and 95% confidence intervals (CIs)were calculated to evaluate the strength of the associations. False positive report possibility (FPRP) analysis were performed to check whether significant results were noteworthy. Results: Significant association with neuroblastoma risk were found for four (rs110419, rs4758051, rs10840002, and rs2168101) out of the five polymorphisms. Combined analysis demonstrated that carriers of 4-5 protective genotypes had a significantly decreased risk of neuroblastoma in comparison those with 0-3 protective genotypes (adjusted OR=0.51, 95% CI=0.39-0.68, P<0.0001). Haplotype analysis of the five SNPs yield four significant haplotypes associated with neuroblastoma susceptibility. Conclusion: In conclusion, we confirmed LMO1 polymorphisms may reduce neuroblastoma risk in eastern Chinese populations.